2021
DOI: 10.3390/diagnostics11091616
|View full text |Cite
|
Sign up to set email alerts
|

CT-Based Risk Stratification for Intensive Care Need and Survival in COVID-19 Patients—A Simple Solution

Abstract: We evaluated a simple semi-quantitative (SSQ) method for determining pulmonary involvement in computed tomography (CT) scans of COVID-19 patients. The extent of lung involvement in the first available CT was assessed with the SSQ method and subjectively. We identified risk factors for the need of invasive ventilation, intensive care unit (ICU) admission and for time to death after infection. Additionally, the diagnostic performance of both methods was evaluated. With the SSQ method, a 10% increase in the affec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The CT imaging characteristics of COVID-19 pneumonia showed 74.3% of patients exhibited peripherally accentuated bilateral consolidations -and this was more extensive in patients intubated or hospitalized at ICUs and opacities in “matte glass” at 89.1%, who rarely showed pleural effusions and lymphadenopathy. 45 The analysis of 23 studies, with a total of 4631 Chinese patients, showed that elevated levels of CK, CK-MB, troponin T/L, LDH and IL-6 and emerging arrhythmia were associated with the development of severe forms of the disease, hospitalization at the ICU or death. 46 …”
Section: Discussionmentioning
confidence: 99%
“…The CT imaging characteristics of COVID-19 pneumonia showed 74.3% of patients exhibited peripherally accentuated bilateral consolidations -and this was more extensive in patients intubated or hospitalized at ICUs and opacities in “matte glass” at 89.1%, who rarely showed pleural effusions and lymphadenopathy. 45 The analysis of 23 studies, with a total of 4631 Chinese patients, showed that elevated levels of CK, CK-MB, troponin T/L, LDH and IL-6 and emerging arrhythmia were associated with the development of severe forms of the disease, hospitalization at the ICU or death. 46 …”
Section: Discussionmentioning
confidence: 99%
“…Using the same method for the semi-quantitative analysis, Hosse et al confirmed that a 10% increase in the affected parenchyma increased the risk for ICU admission (OR 1.68) and for invasive ventilation (OR 1.58), improving early detection of patients at risk for poor outcome compared to subjective assessment [ 49 ]. In their analysis of serial CT features of COVID-19 patients, Li et al stated that critical patients had higher CT scores from the second to the fourth week after onset of symptoms with a peak value of all the features in the third week.…”
Section: Chest Ct As a Prognostic Tool In Covid-19 Patientsmentioning
confidence: 99%